The “Plain facts” of fine paper in “The paradise of bachelors and the tartarus of maids” - Thompson, Graham (Duke University Press, 2012)
This essay intervenes in conversations about mid-nineteenth-century authorship and print culture by distinguishing between the economy of paper and the economy of print. He argues that critical treatments of Melville’s work, and particularly “The Paradise of Bachelors and the Tartarus of Maids” (1855), have not adequately attended to the material economy of paper that existed for Melville before the cycle of literary publication, distribution, and circulation began. Living in the important papermaking region of rural west Massachusetts allowed Melville to experience the raw materials of that economic sector not as a distant or vicarious consumer but, following his visit to the Old Berkshire Mill in Dalton in the winter of 1851, as a specialized purchaser. Instead of treating paper as a metonym of literary-market exchange, then, Thompson’s essay examines Melville’s experience and imagining of this raw material—literally avant la lettre—as a way of better understanding the economy of a substance whose manufactured sizes (folio, octavo, and duodecimo) he had already used to classify whales in Moby-Dick and on which his recalcitrant copyist, Bartleby, refuses to write.